Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja di PT Saputra Empat Srikandi Pemalang - Yeni Dwi Lestari; Farah Chalida Hanoum; Liyandri Rasbina Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of workload and work stress on employee performance with job satisfaction as a mediating variable at PT Saputra Empat Srikandi Pemalang. This research employs a quantitative approach with an associative research design. The population consists of all employees of the company, and the sampling technique used is saturated sampling, in which the entire population is used as respondents. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results indicate that workload and work stress have a negative but non-significant effect on employee performance. In contrast, job satisfaction has a positive and significant effect on employee performance. Furthermore, it was found that workload does not have a significant effect on job satisfaction, while work stress has a significant negative effect on job satisfaction. In the mediation test, job satisfaction is not able to mediate the effect of workload on performance, but it is able to negatively mediate the effect of work stress on employee performance. This study concludes that the improvement of employee performance at PT Saputra Empat Srikandi Pemalang is more significantly influenced by the level of job satisfaction rather than direct workload and work stress. Therefore, proper management of workload and work stress is essential to maintain job satisfaction, which in turn will impact the stability of employee performance.